2011
DOI: 10.2174/156720511794604606
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Brain Endothelium by Soluble Aggregates of the Amyloid-β Protein Involves Nuclear Factor-κB

Abstract: Cerebrovascular accumulation of amyloid-β protein (Aβ) aggregates in Alzheimer's disease (AD) is proposed to contribute to disease progression and brain inflammation as a result of Aβ-induced increases in endothelial monolayer permeability and stimulation of the endothelium for cellular adhesion and transmigration. These deficiencies facilitate the entry of serum proteins and monocyte-derived microglia into the brain. In the current study, a role for nuclear factor-κB (NF-κB) in the activation of cerebral micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 0 publications
2
12
0
Order By: Relevance
“…According to previous data, however, inflammation-inducing agents such as Aβ trigger NF-κB activation in astrocytes (Gonzalez-Velasquez et al, 2011) leading to inflammatory response, and this activation can be inhibited by genistein (Hsieh et al, 2011).…”
Section: Inos Nnos and Astrogliosismentioning
confidence: 87%
“…According to previous data, however, inflammation-inducing agents such as Aβ trigger NF-κB activation in astrocytes (Gonzalez-Velasquez et al, 2011) leading to inflammatory response, and this activation can be inhibited by genistein (Hsieh et al, 2011).…”
Section: Inos Nnos and Astrogliosismentioning
confidence: 87%
“…Isolated soluble A aggregates activated adhesion and transmigration of monocytes, whereas un-aggregated monomers and mature fibrils did not [138]. A further study from the same group also demonstrated an implication of the nuclear factor-kB (NF-kB) in mediating A -induced endothelial permeability to monocytes [140]. A -induced BBB permeability to mononuclear cells has also been demonstrated in vivo.…”
Section: A -Induced Bbb Permeability and Transmigration Of Mononucleamentioning
confidence: 88%
“…A also increases adherence and transmigration of monocytes across the BBB [43, 137,138], mediated by the transcription factor NF-kB [140]. Transmigrated monocytes undergo differentiation into microglia [139], and become activated in inflammatory conditions.…”
Section: A -Endothelium Interactionmentioning
confidence: 99%
“…Aggregated proteins such as TTR and Aβ are cytotoxic and have been confirmed to cause ER stress, oxidative stress, inflammation, anti-angiogenic factor release, inflammation, and apoptosis [67,[87][88][89][90][91][92]. Aβ aggregates are capable of activating glial cells and astrocytes as well as inducing release of proinflammatory cytokines and chemokines such as TNF-α and IL-1β [90][91][92][93]. In addition, Aβ has been shown to activate NF-kB signaling cascade in neurons, astrocytes, glial cells, and brain endothelial cells [92].…”
Section: Misfolded and Aggregated Protein In Preeclampsiamentioning
confidence: 99%
“…Aβ aggregates are capable of activating glial cells and astrocytes as well as inducing release of proinflammatory cytokines and chemokines such as TNF-α and IL-1β [90][91][92][93]. In addition, Aβ has been shown to activate NF-kB signaling cascade in neurons, astrocytes, glial cells, and brain endothelial cells [92].…”
Section: Misfolded and Aggregated Protein In Preeclampsiamentioning
confidence: 99%